Maternal adiposity moderates associations between dietary, serum, and human milk n-3 and n-6 PUFA - Monika A. Zielinska-Pukos; Joanna Bryś; Jadwiga Hamulka (Scientific Reports)
Abstract Overweight and obesity can alter the composition of human milk, including the fatty acid (FA) profile into more proinflammatory state. It is uncertain whether this is due to poor diet quality or the negative effects of obesity on FA metabolism. We examined the associations between dietary, serum, and human milk FA in mothers with normal and excessive body weight and investigated whether adiposity moderates the observed associations. A case-control study was conducted among 40 mothers (20 healthy weight (HW), 20 overweight/obese (OW/OB) 15.5 ± 1.2 weeks postpartum, matched by lactation duration and age. Dietary intake was analyzed based on 3-day food records, and adiposity was assessed by dual-energy X-ray absorptiometry (DXA), serum and human milk FA analyzed by gas chromatography (GC). Overweight/obese mothers had higher dietary and serum trans FA but lower serum arachidonic acid (AA) and human milk docosahexaenoic acid (DHA) compared to normal-weight mothers. Mediation analysis indicated that serum partially mediated the effect of dietary linoleic acid (LA), polyunsaturated fatty acid (PUFA) n-3, and alpha-linolenic acid (ALA) on human milk FA. Adiposity were found to negatively impact the dietary-to-human milk FA association but positively impact serum-to-human milk association. The obesity-related differences in human milk FA profile were not due to dietary differences. Our results suggest human milk PUFA levels may be influenced more by long-term diet than short-term intake, indicating a need for specific dietary guidelines for mothers with higher adiposity to minimze proinflammatory alterations in human milk composition.